2001
DOI: 10.1007/s11934-001-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Posterior urethral valves: Pre- and postnatal management

Abstract: Posterior urethral valves are a common problem encountered by pediatric urologists. The diagnosis is most frequently suggested by antenatal screening ultrasound. A variety of pre- and postnatal parameters have been identified to aid in predicting ultimate renal outcome. These prognostic tools are invaluable to the clinician for counseling parents and for choosing appropriate management. Several approaches to the treatment of patients with posterior urethral valves exist, and the ideal strategy is debatable. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…Die einzelnen konkreten Diagnosen sind epidemiologisch seltener und werden aber auch seltener pränatal erkannt. Originalarbeit rungshäufigkeit, Aszites, bilateraler Nierenbefund) eine wesentliche Verbesserung der prognostischen Einschätzung bei Verdacht auf Urethralklappen bringen [17,18]. Jedoch kann nicht von dem überwiegenden Vorliegen der maximalen Symptomkombination ausgegangen werden [18].…”
Section: Doppelnierenunclassified
“…Die einzelnen konkreten Diagnosen sind epidemiologisch seltener und werden aber auch seltener pränatal erkannt. Originalarbeit rungshäufigkeit, Aszites, bilateraler Nierenbefund) eine wesentliche Verbesserung der prognostischen Einschätzung bei Verdacht auf Urethralklappen bringen [17,18]. Jedoch kann nicht von dem überwiegenden Vorliegen der maximalen Symptomkombination ausgegangen werden [18].…”
Section: Doppelnierenunclassified
“…Furthermore, a group of researchers assessed the impact of prenatal diagnosis and evaluation on the outcome of PUV, and documented that their outcome were not significantly improved [39]. This finding is corroborated in a review which reported that improvement of patient outcome by early detection and antenatal intervention remains to be proven [40]. Some authors however suggest that the onset of ESKD may be prevented or delayed by treating factors like bladder dysfunction, VUR, polyuria and proteinuria responsible for the slow and progressive deterioration in renal function which some of the patients manifest with over a period of time [41].…”
Section: Prenatal Management Of Puvmentioning
confidence: 87%
“…The incidence is between 1 in 5000 and 1 in 8000 male births 1,2 . Langenbeck is credited with first reporting congenital obstruction of prostatic urethra in 1802.Despite this observation, it was left for Hough Hampton Young, more than a century later to define the condition and name it posterior urethral valves 3 .…”
Section: Introductionmentioning
confidence: 99%